Anteseden Dan Konsekuensi Purchase Intention Pada Produk Eco Fashion - Alamsyah, Sarah Amanda Julia; Ekasari, Ayu (Manajemen dan Bisnis, 2025)
This study aims to examine the influence of Environmental Concerns, Social Influence, and Altruism on the Purchase Intention of Eco Fashion, as well as the impact of Purchase Intention on eWOM and Willingness to Pay. An online survey was conducted with 200 respondents who are users of eco fashion products, utilizing Google Forms for data collection. The findings reveal that all three variables positively affect purchase intention. Specifically, environmental concerns enhance consumer awareness of environmental impacts, social influence shapes decisions through social pressure, and altruism drives preferences for sustainable products. Additionally, purchase intention positively impacts eWOM by encouraging consumers to share positive product experiences and increases willingness to pay by strengthening perceived product value. This study recommends that eco fashion businesses leverage these factors in marketing strategies to boost purchase intentions, encourage positive online reviews, and enhance consumers' willingness to pay premium prices.